Simulação da impedância de entrada de uma antena dipolo de meia onda: uma aproximação didática - SILVANO, Guilherme Leite (2018)
With the development of the wireless communication system, the antenna has been widely used. However, there are many characteristic parameters for antennas that need to be calculated to archive achieve an excellent efficiency. For example, the input impedance of antennas. Therefore, it is quite practically to make some simulations to have a view of how the antenna will behave. In order to solve this problem, this thesis establishes the calculation procedure to simulate an half wave dipole antenna using COMSOL. Also make a didactic approach of how to use the program, looking for help furthers projects.